Edge Domination in Web Graph - Omran, A. A.; Al-Harere, M. N. (Journal of College of Education, 2021)
Let {\ \ γ}^e(G) be the edge domination number of a graph. A “web graph” W(s,t) is obtained from the Cartesian product of cycle graph of order s\ and path graph of order\ t. In this paper, edge domination number of the web graph is determined.Mathematical subject classification: 05C69